THE PLANT PERFORMANCES VARIATIONS RECORDING - Karac, Sladana; Belosevic, Svetlana; Sabovljevic, Radovan; Jovanic, Predrag (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
The goal was to define and design, built and test autonomous system for nondestructive recording (monitoring) of the plants performance variations in real time, in laboratory and field conditions. The concept is based on moving, autonomous platform on which, needed/wanted, systems are mounted for analysis and characterization of targeted objects. Practically, with defined system, visual and IR portions of spectra should be covered. First pilot tests are made in the field of Rakovica monastery. The main problem of this heritage object, is that it was built on the water terain, on the underground creeks. So, the watering of plants, during summer, can be problem. The idea was to analyse reaction of the plants existing on the monestery field and their reaction to the additional water. The problmw with Serbian monestiries is that they where built near the water wells,on the terein with number of underground creeks.